Re‐evaluation of prognostic markers including staging, serum free light chains or their ratio and serum lactate dehydrogenase in multiple myeloma patients receiving novel agents. Issue 2 (7th September 2012) - Maltezas, Dimitrios; Dimopoulos, Meletios A.; Katodritou, Irene; Repousis, Panagiotis; Pouli, Anastasia; Terpos, Evangelos; Panayiotidis, Panayiotis; Delimpasi, Sossana; Michalis, Evridiki; Anargyrou, Konstantinos; Gavriatopoulou, Maria; Stefanoudaki, Aikaterini; et al.
Abstract International Staging System (ISS), serum free light chain ratio (sFLCR) and lactate dehydrogenase (LDH) are well known, easily assessed independent prognostic indicators of outcome in multiple myeloma (MM). The purpose of the study was to re‐examine the prognostic contribution of these variables in a multicenter setting with special attention to MM patients treated with autologous stem cell transplantation (ASCT) or novel agents (NA). Three hundred and five symptomatic newly diagnosed MM patients were retrospectively studied. Twenty‐seven per cent, 32% and 41% were in ISS stages 1, 2, and 3, respectively. Fifty‐six per cent of them presented kappa light chain monoclonality; median sFLCR was 27.04 (0.37–1.9 × 105) and 47.97 (0.26–2.3 × 107) for kappa patients and lambda patients, respectively; patients with sFLCR above median constituted the high sFLCR group. Thirty‐one per cent of patients had increased LDH. As first line treatment, 55.7% received conventional treatment and 44.3% NA. After induction, 24% underwent ASCT, whereas 76% received NA at any line, either bortezomib (82.5%), thalidomide (48%) or lenalidomide (27%). When the 305 patients were analyzed together, staging, high sFLCR and abnormal LDH were predictive of survival. The same was true for patients that never received NA, whereas neither high sFLCR nor abnormal LDH constituted adverse factors in patients that received NA frontline. In the last group of patients, no difference was observed between ISS stages 2 and 3. The median 5‐year survival of patients that never received NA versus those who did frontline was 29% vs 47%, 7% vs 52% and 24% vs 40% in patients with abnormal LDH, high sFLCR and ISS stage 3, respectively (p = 0.03, p < 0.00001 and p = 0.035). In conclusion, patients gaining the most from NA are those with an aggressive disease as reflected by advanced stage, abnormal LDH and high sFLCR. In addition, the adverse impact of these three variables is obscured by NA. Copyright © 2012 John Wiley & Sons, Ltd.